EFEKTIVITAS SUHU OPTIMUM PENETASAN TELUR LOBSTER AIR TAWAR (Cherax quadricarinatus) PADA BERBAGAI FASE PERKEMBANGAN EMBRIO - Panggabean, Immanuel Perdinan; Komariyah, Siti; Haser, Teuku Fadlon (Jurnal Perikanan Unram, 2024)
Freshwater lobster (Cherax quadricarinatus) is a freshwater fishery commodity that is very promising as a substitute for seawater lobster. The egg hatching process is one of the factors that really determines the success of freshwater lobster cultivation activities. The aim of this research was to evaluate the percentage of eggs hatching degree and survival of freshwater lobster seeds hatched using the incubation method. This research used a completely randomized design method with 4 treatments and 3 replications. Treatment A as control (natural hatching of lobster eggs), Treatment B (incubation phase 2 or 4-6 days after fertilization), Treatment C (incubation phase 4 or 10-12 days after fertilization), Treatment D (incubation phase 6 or 16-18 days after fertilization). The test eggs used in this study were obtained from the same parent. Meanwhile, natural hatching uses eggs from different parents. The results showed that the degree of hatchability of naturally hatched and incubated lobster eggs was significantly different (p<0.05). In incubation hatching, the best egg hatching rate was in phase 4, namely 91.1 ± 3.85a with a seed survival rate of 91.66 ± 14.43a. Thus, hatching of freshwater lobster eggs at various stages of embryonic development with an optimum temperature of 30°C should be carried out in phase 4 or 10-12 days after fertilization with an egg hatching time of 33 days.